Pertussis resurgence: epidemiological trends, pathogenic mechanisms, and preventive strategies - Sheng, Yaping; Ma, Shengjie; Zhou, Qi; Xu, Jiancheng (Frontiers in Immunology, 2025)
Pertussis, also known as whooping cough, is a highly contagious acute respiratory infection primarily caused by Bordetella pertussis. Although this disease can occur at any age, infants and young children remain the most vulnerable to severe illness and mortality. Moreover, epidemiological trends indicate a notable shift in the incidence of pertussis over time, with an increasing number of reported cases in adolescents and adults. During the 1950s, the widespread implementation of whole-cell pertussis (wP) vaccines significantly reduced the incidence and mortality associated with pertussis. Despite their effectiveness, the frequent adverse reactions linked to wP vaccines prompted a shift towards the utilization of acellular pertussis (aP) vaccines, which have a lower reactogenicity. However, over the past two decades, several countries with a high coverage of aP vaccines have experienced a notable rise in the incidence of pertussis, a phenomenon called pertussis resurgence. The causes of this resurgence are multifactorial and highly complex. Notably, the peak incidence of pertussis has shifted from the infant population to adolescents and adults, who now serve as the primary sources of infection in infants. Such a shift raises critical concerns regarding the current and future control of pertussis. The lack of comprehensive understanding of its pathogenesis is a significant contributing factor to this public health challenge. Although extensive research on the pathogenesis of pertussis has been conducted, it remains an issue without appropriate animal models that effectively replicate the symptomatology commonly observed in human cases. This review provides an overview of B. pertussis epidemiology and recent pathogenesis advances. It further analyzes the potential causes and contributing elements responsible for the resurgence of pertussis. Lastly, the review proposes evidence-based strategies aimed at enhancing public awareness and implementing effective measures to prevent the risk of unexpected outbreaks.